Preliminary analysis of investigation Radio Frequency Interference (RFI) profile analysis at Universiti Teknologi MARA - Roslan, Umar; Hamidi, Z.S.; Abidin, Z.Z.; Ibrahim, Z.A.; Shariff, N.N.M.; Ibrahim, U.F.S.U (2011)
In this paper, we have identified some important Radio Frequency Interference (RFI) sources that can potentially be a problem for any future radio astronomical observations in Universiti Teknologi MARA (UiTM) and possibly in Malaysia as a whole. Analysis is done by classifying and characterizing the strength of the sources' RFI profiles. Comparison of the RFI profiles between the indoor (Faculty of Applied Sciences) and outdoor (Square Parade) areas are also presented.Some suggestions in improving the quality of radio frequency profile are recommended.